The Effect of Optimal Cash and Deviation from Target Cash on the Firm Value: Empirical Study in Indonesian Firms - HC, R Heru Kristanto; Hanafi, Mamduh M; Lantara, Wayan Nuka (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2019)
The aim of this paper is to examine the effect of cash, optimal cash holding, deviation from target cash (the target adjustment model) on the firm value. This research uses a sample of Indonesian publicly traded firms for the period 2001-2017 (3,349 observation). This paper uses a dynamic panel fixed effects model to estimate optimal cash holdings. Hypothesis testing uses GLS fixed effect and interaction effect uses regression moderated analysis. Research finds that: first, cash, optimal cash, and deviation from target cash have an effect on the firm value. Second, corporate governance moderates the effect of cash, optimal cash, and deviation from target cash on the firm value. Third, investment positively moderates the effect of cash on the firm value. Investment negatively moderates the effect of optimal cash, deviation from target cash on the firm value. Debt negatively moderates the effect of cash, optimal cash on the firm value. Debt positively moderates the effect of deviation from target cash on the firm value.Ã‚Â